American Aniline Products Dye Sample Box
A red display box of 24 samples of various products colored with dyes. The top and side flaps open to reveal 24 samples of various products colored with dyes. Includes liquids in small bottles, powders in brass circular containers, matches, and wood. The inside of the box shows the dyeing application formula for each product. This sample box may have been manufactured by the American Aniline Works, a short-lived company founded circa 1870 and destroyed by a flood of the Kanawha River by c. 1880.
Keywords: American Aniline Products; Dyes and dyeing; Dyes and dyeing--Equipment and supplies; Aniline; Dyes and dyeing--Chemistry; Formulas, recipes, etc.; Samples (Commerce)